Non-Linear Effects of Acute Sleep Deprivation on Spatial Working Memory: Cognitive Depletion and Neural Compensation - Yongcong Shao; Lin Xu; Ziyi Peng; Xin An; Jingjing Gong; Mengfei Han (Brain Sciences)
Background: Spatial working memory is crucial for processing visual and spatial information, serving as a foundation for complex cognitive tasks. However, the effects of prolonged sleep deprivation on its dynamics and underlying neural mechanisms remain unclear. This study aims to investigate the specific trends and neural mechanisms underlying spatial working memory alterations during 36 h of acute sleep deprivation. Methods: Twenty participants underwent a 36 h protocol of acute sleep deprivation. Utilizing the spatial 2-back task for assessing spatial working memory, combined with event-related potential (ERP) technology, we compared behavioral and neural responses at four critical time points—before deprivation, and after 12, 24, and 36 h of sleep deprivation—to uncover dynamic cognitive changes. Results: The findings indicate that the impact of sleep deprivation on spatial working memory exhibits significant temporal dependence. After 24 h of deprivation, both behavioral performance and ERP component amplitudes showed significant declines. During the period from 24 to 36 h, the amplitudes of the P2, N2, and P3 components exhibited a recovery trend, potentially reflecting neural compensatory mechanisms. Conclusions: The impact of 36 h acute sleep deprivation on spatial working memory is characterized by time-dependent and phase-specific effects. Initially, sleep deprivation leads to severe cognitive depletion, followed by an adaptive compensatory phase where neural mechanisms may partially restore function. These findings highlight the non-linear nature of cognitive impairment due to sleep deprivation, involving complex self-regulatory and compensatory mechanisms, with implications for understanding cognitive resilience and adaptive processes.